Outcomes and costs in specialized burn care: Adapting the Quality Cost Indicator (QCI) model for burn care - Raaba S. M. Thambithurai; Willem H. P. van Veghel; Denise van Uden; Jean-Bart Bügel; Anouk Pijpe; Marianne K. Nieuwenhuis; Cornelis H. van der Vlies; Margriet E. van Baar; Angelique E. A. M. Weel-Koenders (PLoS ONE, 2025)
The Quality Cost Indicator (QCI) model supports value-based health care at the institutional level, by calculating disease-specific health outcomes per unit cost over time. The aim of this study was to adapt the QCI model for specialized burn care (the BC-QCI model) and explore its utilization using real-world data. Burn care outcome indicators were selected through an iterative process with multiple stakeholders. Threshold values were established per outcome indicator and average total healthcare costs were calculated. A cohort of adult burn patients (n = 1449) admitted for at least one day and/or had undergone surgery in Dutch burn centers between 2020 and 2023 was used, with a follow-up period of 12 months. The proportion of patients who achieved textbook outcome (i.e., having achieved all the outcome indicators), the average total costs per patient, and QCI values were calculated. Of all patients, 54% achieved all five outcome indicators (i.e., length of stay, wound infections, other complications, discharge destination, and predicted mortality). The most successful outcome indicator was ‘predicted mortality’ (passed by 99% of the population), the least successful outcome indicator was ‘length of stay’ (62%). The patients who failed to achieve one or more outcome indicators (46%) had significantly higher average total costs compared to the patients who achieved textbook outcome (54%) (€50,134 [€47,810-€52,850] vs. €11,721 [€11,096-€12,429]). The BC-QCI model is a solid foundation to provide insights into the outcomes and costs for specialized burn care at the institutional level.